Enhancement Of Dissolution Rate Studies On Solid Dispersion Of Aceclofenac - DR.K.L.SENTHILKUMAR,; Y.SIRISHA, (International Journal of Pharma and Bio Sciences, 2011)
Aceclofenac is a Non- Steroidal Anti Inflammatory drug indicated for the relief of pain and inflammation, associated with rheumatoid arthritis, osteo arthritis, ankylosing, spondylitis. The percentage of dissolution rate of drug released from pure Aceclofenac was obtained 26.48% in 180min. The aim of the study was to enhance the dissolution rate on solid dispersion of Aceclofenac by using PEG6000 as carrier in three different ratios such as ACF:PEG6000-1:1, 1:2 and 1:4 by fusion method or melting method. The percentage of drug release of Aceclofenac from solid dispersions ACF:PEG6000-1:1,1:2 and 1:4 was 59.65%,84.75%,98.34% respectively in 180min. Aceclofenac from solid dispersions due to enhancing effect of PEG6000.